A papermaking process for white board paper composite sizing
Patent Information
- Application Number
- CN202610546807.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-04-23
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种白板纸复合配浆造纸工艺,解决了现有技术因废纸纤维角质化程度高、缺乏有效的构象锁定手段以及界面结合网络强度不足,导致成纸力学强度偏低且造纸白水有机污染负荷较重的问题
1、本发明通过工业尿素水溶液对废纸原料进行干区高浓浸渍,并结合后续的中性高温热力学解构过程,利用尿素分子的强离液特性实现了对角质化纤维内氢键的竞争性置换,有效恢复纤维润胀性能,避免强碱对纤维素共价键的破坏,从而限制了纤维素与半纤维素的降解,降低造纸机网部冷白水中的有机污染负荷。
Smart Images

Figure CN122344845B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of papermaking processing technology, specifically to a whiteboard paper composite pulping and papermaking process. Background Technology
[0002] After repeated wet-dry cycles, waste paper fibers undergo irreversible keratinization due to physical shrinkage caused by hydrogen bonds within their cell walls, resulting in a significant decrease in the fibers' swelling properties and water retention capacity. Currently, the industry commonly forces chemical swelling of fibers in a strongly alkaline environment. However, this process is accompanied by the non-selective degradation of lignin and hemicellulose, which not only destroys the fiber's own covalent bond structure and reduces the strength of the paper skeleton, but also causes a large amount of dissolved organic matter to flow into the white water system, increasing the chemical oxygen demand (COD) load within the closed-loop system.
[0003] In actual production processes, even if the pulping temperature is increased or chemical agents are added to induce instantaneous swelling of the fibers, the pulp will rapidly revert to its original conformation during subsequent cooling or pumping due to the lack of effective measures to fix the microstructure. This makes it difficult for subsequently added chemical reinforcing agents to penetrate into the fiber cell walls, causing them to remain mostly on the fiber surface. This results in insufficient agent utilization and periodic fluctuations in the physical properties of the finished paper. Maintaining the fibers in a stable swollen conformation is currently a key technical challenge in waste paper recycling processes.
[0004] Current paper strengthening solutions are mostly based on the theory of charge adsorption. However, when dealing with complex waste paper pulp, electrostatic bonding alone is insufficient to overcome the interference of anionic waste in the white water system. Because it is impossible to build a stable network with anti-interference capabilities at the fiber interface, the ring crush index and interlayer bonding strength of the whiteboard base paper are limited. Furthermore, the practice of compensating for strength by adding excessive amounts of additives, in turn, worsens the circulation environment of the white water system, creating a technical contradiction between performance improvement and environmental protection. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a whiteboard paper composite pulping and papermaking process, which solves the problems of low mechanical strength of paper and heavy organic pollution load in papermaking white water caused by the high degree of keratinization of waste paper fibers, lack of effective conformation locking means, and insufficient interfacial bonding network strength in existing technologies.
[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a whiteboard paper composite pulping and papermaking process, comprising the following steps: Waste paper raw materials are subjected to high-concentration impregnation in a dry zone by atomizing and spraying industrial urea aqueous solution to obtain pre-impregnated waste paper raw materials. Pre-impregnated waste paper raw materials are injected into hot water for neutral high-temperature thermodynamic decomposition to obtain high-temperature medium-concentration pulp; Cold white water from the wire section of a paper machine is mixed into a high-temperature, medium-concentration pulp to achieve rapid cooling and conformation locking of the cold white water, resulting in a cooled, diluted pulp. Anhydrous calcium chloride solution is injected into the cooled and diluted slurry through a turbulent staggered dosing system, and the pre-crosslinked slurry is obtained by high-frequency turbulent shearing by the impeller of the slurry pump. Amphoteric starch solution is added dropwise to the pre-crosslinked slurry, and pulse coordination crosslinking is completed by high-frequency fluid pulse shearing through a pressure screen rotor to obtain the crosslinked slurry; The cross-linked pulp is dehydrated and shaped to obtain a wet paper web; the wet paper web is then heat-shrinked, cured, and dried to obtain the whiteboard base paper.
[0007] In the above technical solution, the dosage of each component is calculated based on the dry weight of waste paper pulp: the dry weight of industrial urea is 1.0%-1.5%, the dry weight of anhydrous calcium chloride is 0.2%-0.3%, and the dry weight of amphoteric starch is 1.2%-1.5%.
[0008] Preferably, the industrial urea aqueous solution has a mass concentration of 20%-30%; the anhydrous calcium chloride solution has a mass concentration of 5%-10%; the amphoteric starch gel has a mass concentration of 1%-2%; and the total degree of substitution of the amphoteric starch for its anions and cations is 0.03-0.05.
[0009] Preferably, the waste paper raw material is selected from one or more of old corrugated cardboard boxes, mixed waste paper, and waste newspapers. High-concentration impregnation in the dry zone is performed on a conveyor belt, with a natural surface penetration time of 2-3 minutes.
[0010] Neutral high-temperature thermodynamic decomposition is performed inside the hydraulic pulper, with the injected hot water temperature at 65℃-70℃, the pulp mass concentration controlled at 8%-12%, and the system pH maintained at 6.5-7.5. Hydraulic pulping is carried out continuously for 15-20 minutes at a mixed temperature of 55℃-60℃.
[0011] The rapid cooling conformation of the cold white water is locked along the pumping line and at the inlet of the pulping tank. The volume ratio of the high-temperature medium-concentration pulp to the cold white water in the paper machine wire section is 1:2 to 1:3. The temperature of the cold white water in the paper machine wire section is 20℃-25℃. The system temperature is reduced to below 30℃ within 1 minute, and the concentration is diluted to 3%-4%.
[0012] Preferably, the shear rate of the high-frequency turbulent shear is greater than or equal to 1000 s⁻¹. -1 Amphoteric starch is prepared through a process including starch milk preparation, cationization reaction, anionization reaction, neutralization washing, and drying.
[0013] By adopting the above technical solution, the present invention achieves systematic optimization from fiber microstructure repair to macro network construction in the production process of whiteboard paper base paper. Its core mechanism lies in the thermodynamic decoupling of intermolecular forces and coordination assembly under dynamic flow field.
[0014] In the high-concentration impregnation stage in the dry zone, the choice of industrial urea aqueous solution is not simply as a wetting agent. This solute, with its strong liquid-leaching properties, plays a crucial role in the subsequent neutral high-temperature thermodynamic decomposition process. As the temperature inside the hydraulic pulper rises, industrial urea molecules, driven by thermal energy, intervene in the cellulose chain segments. The carbonyl and amino groups in its molecular structure, through a competitive binding mechanism, directly interfere with and block the originally dense, irreversible keratinized internal hydrogen bonds within the cellulose.
[0015] This chemical process causes the originally closed pores of the fiber cell wall to expand again, forming a metastable open conformation of fibers with high swelling, which increases the effective specific surface area of the fibers and the exposure of free hydroxyl groups.
[0016] This process rapidly reduces the system's heat energy within one minute by instantly incorporating cold white water into the wire section of a large-volume paper machine. This forced cooling intervention restricts the rearrangement pathways of the cellulose molecular chains, locking their structure in a highly swollen metastable state. Maintaining this state ensures that subsequent chemical agents can penetrate unimpeded deep into the fiber, reserving space for building a high-performance crosslinking network.
[0017] Based on this, the ordered assembly of the three-dimensional ion coordination network becomes the mechanical pillar for improving paper strength. During the turbulent displacement dosing process in the flow delivery system, the Ca released from the anhydrous calcium chloride solution... 2+ The high-frequency turbulent shearing of the impeller of the slurry pump overcomes the shielding effect caused by uneven charge distribution, and the anionic charge sites on the fiber surface are uniformly and densely anchored, establishing a stable coordination center.
[0018] Subsequently, the added amphoteric starch solution, under the pulsed shear force generated by the pressure screen rotor, undergoes physical expansion of its macromolecular chains, exposing a large number of phosphate ester anionic groups. These groups react with the pre-placed Ca... 2+ The coordination center generates specific multiple coordination bonds, while the quaternary ammonium cationic groups are held in place at the residual anionic sites of the fiber by electrostatic adsorption.
[0019] This complex network spanning the fiber interface exhibits strong structural responsiveness during the final heat shrinkage curing and drying stages. As moisture evaporates, the three-dimensional ionic coordination network undergoes irreversible thermal shrinkage and physical compaction under the influence of heat, strongly pulling together and solidifying the dispersed fiber components. This bonding mode changes the fragile nature of traditional paper, which relies solely on hydrogen bonds for support, by using a high-strength ionic coordination framework.
[0020] By coupling the temperature field and the shear flow field in this way, the process repairs the keratinization defects of waste paper fibers without damaging the covalent bonds of the fibers, improves the ring crush strength index and interlayer bonding strength of the whiteboard paper base paper, and significantly reduces the pollution load of cold white water in the wire section of the papermaking machine by avoiding the strong alkaline environment.
[0021] This invention provides a process for compounding and papermaking of whiteboard paper. It has the following beneficial effects: 1. This invention uses industrial urea aqueous solution to impregnate waste paper raw materials in a dry zone with high concentration, and combines it with a subsequent neutral high-temperature thermodynamic deconstruction process. By utilizing the strong liquid-dissociating properties of urea molecules, competitive replacement of hydrogen bonds in keratinized fibers is achieved, effectively restoring fiber swelling performance, avoiding the destruction of cellulose covalent bonds by strong alkali, thereby limiting the degradation of cellulose and hemicellulose, and reducing the organic pollution load in the cold white water of the paper machine wire section.
[0022] 2. This invention utilizes cold white water in the wire section of a paper machine to achieve instantaneous cooling and conformational quenching and locking, which restricts the rearrangement behavior of cellulose molecular chains during the slow cooling process. This keeps the fiber in a metastable open conformation that is conducive to chemical penetration, providing a channel for subsequent anhydrous calcium chloride solution and amphoteric starch solution to enter the pores inside the fiber. This overcomes the insufficient utilization of reagents and the periodic fluctuations in paper strength caused by the spontaneous retraction of the fiber conformation.
[0023] 3. Based on the turbulent misaligned dosing of the flow delivery system and the pulse coordination crosslinking step, the present invention forms a dense three-dimensional ion coordination network, realizing the orderly anchoring of chemical components. The compression force generated by the network during the heat shrink curing process solidifies the originally loose fiber components into a rigid skeleton with high compressive strength, thereby improving the ring crush strength index and interlayer bonding strength of the obtained whiteboard paper base paper. Attached Figure Description
[0024] Figure 1 The infrared spectrum of the fiber swelling and conformational locking mechanism in the test example of the present invention; Figure 2 The UV-Vis scan spectrum of the cold white water in the wire section of the paper machine is a test example of the present invention. Detailed Implementation
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Preparation Examples 1-3: Preparation Example 1: This preparation example provides a method for preparing amphoteric starch, including the following steps: Step 1: Take industrial raw starch (tapioca starch is selected), add it to room temperature water and mechanically mix it to obtain a starch milk with a mass concentration of 35%.
[0027] Step 2: Add a 3% sodium hydroxide solution to the starch milk to adjust the pH of the system to 11.0. Then, slowly add 3-chloro-2-hydroxypropyltrimethylammonium chloride (2.5% of the dry starch mass) dropwise. Heat the mixture to 45°C and keep it at a constant temperature for 4 hours to obtain cationic starch milk.
[0028] Step 3: Add sodium tripolyphosphate (0.8% of the dry starch mass) to the cationic starch milk, keep the reaction system at a constant temperature of 45°C for 2 hours to obtain amphoteric starch slurry.
[0029] Step 4: Add 10% dilute hydrochloric acid to the amphoteric starch slurry to adjust the pH of the system to 6.0 for neutralization to terminate the reaction. Then, centrifuge to dehydrate and wash twice with water. Finally, use an airflow dryer at 60°C to evaporate the water to less than 12% to obtain amphoteric starch (the total degree of substitution of anions and cations was determined to be 0.03).
[0030] Preparation Example 2: This preparation example provides a method for preparing amphoteric starch, including the following steps: Step 1: Take industrial raw starch (selected as a physical mixture of cassava starch and corn starch), add it to room temperature water and mechanically mix it to obtain a starch milk with a mass concentration of 38%.
[0031] Step 2: Add a 3% sodium hydroxide solution to the starch milk obtained in Step 1 to adjust the pH of the system to 11.2. Then, slowly add 3-chloro-2-hydroxypropyltrimethylammonium chloride (3.0% of the dry starch mass) dropwise. Heat the mixture to 48°C and keep it at a constant temperature for 5 hours to obtain cationic starch milk.
[0032] Step 3: Add sodium tripolyphosphate (1.0% of the dry starch mass) to the cationic starch milk obtained in Step 2, keep the reaction system at a constant temperature of 48°C for 2.5 hours to obtain amphoteric starch slurry.
[0033] Step 4: Add 10% dilute hydrochloric acid to the amphoteric starch slurry obtained in Step 3 to adjust the pH of the system to 6.2 for neutralization to terminate the reaction. Then, centrifuge to dehydrate and wash with water 3 times. Finally, use an airflow dryer at 60°C to evaporate the water to less than 12% to obtain amphoteric starch (the total degree of substitution of anions and cations was determined to be 0.04).
[0034] Preparation Example 3: This preparation example provides a method for preparing amphoteric starch, including the following steps: Step 1: Take industrial raw starch (choose: corn starch), add it to room temperature water and mechanically mix to obtain a starch milk with a mass concentration of 40%.
[0035] Step 2: Add a 3% sodium hydroxide solution to the starch milk to adjust the pH of the system to 11.5. Then, slowly add 3-chloro-2-hydroxypropyltrimethylammonium chloride (3.5% of the dry starch mass) dropwise. Heat the mixture to 50°C and keep it at a constant temperature for 6 hours to obtain cationic starch milk.
[0036] Step 3: Add sodium tripolyphosphate (1.2% of the dry starch mass) to the cationic starch milk, keep the reaction system at a constant temperature of 50°C for 3 hours to obtain amphoteric starch slurry.
[0037] Step 4: Add 10% dilute hydrochloric acid to the amphoteric starch slurry to adjust the pH of the system to 6.5 for neutralization to terminate the reaction. Then, centrifuge to dehydrate and wash with water three times. Finally, use an airflow dryer at 60°C to evaporate the water to less than 12% to obtain amphoteric starch (the total degree of substitution of anions and cations was determined to be 0.05).
[0038] Examples 1-3: Example 1: This embodiment provides a whiteboard paper composite pulping and papermaking process, including the following steps: Step 1: Place the waste paper raw material (selected: waste newspaper) on the conveyor belt, and use a spraying device to atomize and spray the industrial urea aqueous solution (mass concentration of 20%, based on the dry weight of industrial urea, the amount used is 1.0% of the oven-dry pulp mass of the waste paper raw material) onto the surface of the waste paper raw material. Control the belt running speed to keep the surface naturally penetrated for 2 minutes to obtain the pre-impregnated waste paper raw material.
[0039] Step 2: Put the pre-impregnated waste paper raw material into the hydrator, inject hot water at a temperature of 65°C, control the pulp mass concentration in the hydrator to 9%, maintain the natural pH of the system at 6.5, and continuously hydrator pulp for 15 minutes at a mixing temperature of 55°C to finally obtain high-temperature medium-concentration pulp.
[0040] Step 3: Pump the high-temperature medium-concentration pulp into the pulping tank. Along the pumping line and at the inlet of the pulping tank, instantaneously mix in the paper machine wire section cold white water at a volume ratio of 1:2, which is 20°C. Within 1 minute, the system temperature drops rapidly to 28°C, and the concentration is diluted to 3%, thus obtaining the cooled and diluted pulp.
[0041] Step four: Pump the cooled and diluted pulp into the delivery pipeline. Inject anhydrous calcium chloride solution (5% by mass concentration, calculated as 0.2% of the dry weight of the waste paper pulp) before the inlet negative pressure zone of the slurry pump. The pulp is then subjected to high-frequency turbulent shearing (shear rate ≥1000s) by the impeller of the slurry pump. -1 This process achieves microsecond-level instantaneous mixing and further dilutes the mixture to a concentration of 1.2% in a slurry pump to obtain a pre-crosslinked slurry.
[0042] Step 5: Amphoteric starch solution (prepared by gelatinizing the amphoteric starch obtained in Preparation Example 1, with a mass concentration of 1%, and the amount used is 1.2% of the dry weight of waste paper pulp based on the dry weight of the amphoteric starch) is continuously added dropwise to the pre-crosslinked slurry. The mixture flows into a pressure screen, and under the high-frequency fluid pulse shearing action generated by the pressure screen rotor, the polymer chains are extended and the three-dimensional ion coordination network crosslinking is completed to obtain the crosslinked slurry.
[0043] Step 6: The cross-linked slurry is sprayed into the headbox and subjected to gravity dewatering and vacuum dewatering on the forming wire of the paper machine in sequence to obtain a wet paper web with preliminary wet strength.
[0044] Step 7: The wet paper web is fed into the press section and the drying cylinder. Under the heat transfer action at 80°C, the cross-linked network undergoes irreversible thermal shrinkage and physical compression. As the internal moisture evaporates, it is finally wound up to obtain the target product of this process: whiteboard paper base paper.
[0045] Example 2: This embodiment provides a whiteboard paper composite pulping and papermaking process, including the following steps: Step 1: Place the waste paper raw material (mixed waste paper is selected) on the conveyor belt, and use a spraying device to spray the industrial urea aqueous solution (mass concentration of 25%, based on the dry weight of industrial urea, the amount used is 1.2% of the dry pulp mass of the waste paper raw material) onto the surface of the waste paper raw material. Control the belt running speed to keep the surface naturally penetrated for 2.5 minutes to obtain the pre-impregnated waste paper raw material.
[0046] Step 2: Put the pre-impregnated waste paper raw material into the hydrator, inject hot water at a temperature of 68°C, control the pulp mass concentration in the hydrator to 10%, maintain the natural pH of the system at 7.0, and continuously hydrator pulp for 18 minutes at a mixing temperature of 58°C to finally obtain a high-temperature medium-concentration pulp.
[0047] Step 3: Pump the high-temperature medium-concentration pulp into the pulping tank. Along the pumping line and at the inlet of the pulping tank, instantaneously mix in the paper machine wire section cold white water at a volume ratio of 1:2, which is 22°C. Within 1 minute, the system temperature drops sharply to 29°C, and the concentration is diluted to 3.3%, thus obtaining the cooled and diluted pulp.
[0048] Step four: Pump the cooled and diluted pulp into the delivery pipeline. Inject anhydrous calcium chloride solution (8% by mass concentration, calculated as 0.25% of the dry weight of the waste paper pulp) before the inlet negative pressure zone of the slurry pump. The pulp is then subjected to high-frequency turbulent shearing (shear rate ≥1000s) by the impeller of the slurry pump. -1 This process achieves microsecond-level instantaneous mixing and further dilutes the mixture to a concentration of 1.0% in a slurry pump to obtain a pre-crosslinked slurry.
[0049] Step 5: Amphoteric starch solution (prepared by gelatinizing the amphoteric starch obtained in Preparation Example 2, with a mass concentration of 1.5%, and the amount used is 1.3% of the dry weight of waste paper pulp based on the dry weight of amphoteric starch) is continuously added dropwise to the pre-crosslinked slurry. The mixture flows into a pressure screen, and under the high-frequency fluid pulse shearing action generated by the pressure screen rotor, the polymer chains are extended and the three-dimensional ion coordination network crosslinking is completed to obtain the crosslinked slurry.
[0050] Step 6: The cross-linked slurry is sprayed into the headbox and subjected to gravity dewatering and vacuum dewatering on the forming wire of the paper machine in sequence to obtain a wet paper web with preliminary wet strength.
[0051] Step 7: The wet paper web is fed into the press section and the drying cylinder. Under the heat transfer action at 95°C, the cross-linked network undergoes irreversible thermal shrinkage and physical compression. As the internal moisture evaporates, it is finally wound up to obtain the target product of this process: whiteboard paper base paper.
[0052] Example 3: This embodiment provides a whiteboard paper composite pulping and papermaking process, including the following steps: Step 1: Place the waste paper raw material (using old corrugated cardboard boxes) on the conveyor belt, and use a spraying device to atomize and spray the industrial urea aqueous solution (mass concentration of 30%, based on the dry weight of industrial urea, the amount used is 1.5% of the dry pulp mass of the waste paper raw material) onto the surface of the waste paper raw material. Control the belt running speed to keep the surface naturally penetrated for 3 minutes to obtain the pre-impregnated waste paper raw material.
[0053] Step 2: Put the pre-impregnated waste paper raw material into the hydrapulper, inject hot water at a temperature of 70°C, control the pulp mass concentration in the hydrapulper to 12%, maintain the natural pH of the system at 7.5, and continuously hydrapulp at a mixing temperature of 60°C for 20 minutes to finally obtain a high-temperature medium-concentration pulp.
[0054] Step 3: Pump the high-temperature medium-concentration pulp into the pulping tank. Along the pumping line and at the inlet of the pulping tank, instantaneously mix in the paper machine wire section cold white water at a volume ratio of 1:3, which is 25°C. Within 1 minute, the system temperature drops sharply to below 30°C, and the concentration is diluted to 3%, thus obtaining the cooled and diluted pulp.
[0055] Step four: Pump the cooled and diluted pulp into the delivery pipeline. Inject anhydrous calcium chloride solution (mass concentration of 10%, based on the dry weight of anhydrous calcium chloride, the amount used is 0.3% of the oven-dry pulp mass of the waste paper raw material) before the inlet negative pressure zone of the pulping pump. The pulp is then subjected to high-frequency turbulent shearing (shear rate ≥1000s) by the impeller of the pulping pump. -1 This process achieves microsecond-level instantaneous mixing and further dilutes the mixture to a concentration of 0.8% in a slurry pump to obtain a pre-crosslinked slurry.
[0056] Step 5: Amphoteric starch solution (prepared by gelatinizing the amphoteric starch obtained in Preparation Example 3, with a mass concentration of 2%, and the amount used is 1.5% of the dry weight of waste paper pulp based on the dry weight of the amphoteric starch) is continuously added dropwise to the pre-crosslinked slurry. The mixture flows into a pressure screen, and under the high-frequency fluid pulse shearing action generated by the pressure screen rotor, the polymer chains are extended and the three-dimensional ion coordination network crosslinking is completed to obtain the crosslinked slurry.
[0057] Step 6: The cross-linked slurry is sprayed into the headbox and subjected to gravity dewatering and vacuum dewatering on the forming wire of the paper machine in sequence to obtain a wet paper web with preliminary wet strength.
[0058] Step 7: The wet paper web is fed into the press section and the drying cylinder. Under the action of heat transfer at 110°C, the cross-linked network undergoes irreversible thermal shrinkage and physical compression. As the internal moisture evaporates, it is finally wound up to obtain the target product of this process: whiteboard paper base paper.
[0059] Comparative Examples 1-5: Comparative Example 1: Compared with Example 2, the differences are: no dry-zone high-concentration impregnation (i.e. no spraying of industrial urea aqueous solution), the natural pH of the system is changed to strong alkalinity in step two (by adding conventional sodium hydroxide solution), and the amphoteric starch solution is replaced with commercially available conventional cationic starch solution of the same mass concentration in step five. All other aspects are the same.
[0060] Comparative Example 2: Compared with Example 2, the difference is that in the high-concentration impregnation of the dry area in step one, the sprayed industrial urea aqueous solution is replaced with an equal volume of clean water, and the rest are the same.
[0061] Comparative Example 3: Compared with Example 2, the difference is that the rapid cooling conformation locking step of the paper machine wire section cold white water is missing. That is, after the high temperature medium-concentration pulp obtained in Step 2 is pumped to the pulp tank, it is not mixed with the paper machine wire section cold white water. Instead, the system is allowed to cool down naturally and slowly to 29°C and diluted to 3.3% with only water. Everything else is the same.
[0062] Comparative Example 4: Compared with Example 2, the difference is that instead of using a slurry pump and pressure screen for turbulent displacement dosing and pulse coordination crosslinking in the flow delivery system, anhydrous calcium chloride solution and amphoteric starch slurry are simultaneously injected into the slurry tank and mixed under conventional low-shear stirring. All other aspects are the same.
[0063] Comparative Example 5: Compared with Example 2, the difference is that in step five, the amphoteric starch solution is replaced with an equal amount of conventional monocationic starch solution (lacking phosphate ester anionic groups), while the rest are the same.
[0064] Test Examples 1-4: Test Example 1: Feasibility Test of Fiber Swelling and Conformation Hardening Locking Mechanism Experimental steps: Waste paper raw materials before high-consistency impregnation in the dry zone in Example 2 (denoted as samples A-1 and A-2), high-temperature medium-consistency pulp after neutral high-temperature thermodynamic deconstruction (denoted as samples B-1 and B-2), and cooled diluted pulp after conformational locking by cold white water in the paper machine wire section (denoted as samples C-1 and C-2) were extracted respectively. At the same time, two samples of pulp that were not conformationally locked by cold white water in the paper machine wire section and were naturally and slowly cooled to room temperature were taken as control samples (denoted as samples D-1 and D-2). The sample weight of each group was guaranteed to be no less than 2g of oven-dry fiber.
[0065] The extracted pulp samples from each stage were thoroughly diluted in deionized water and centrifuged at 3000 r / min for 15 min to remove free water from the fiber surface while retaining bound water and capillary water inside the fiber cell walls and pores.
[0066] After centrifugation, the wet pulp blocks of each sample were quickly removed and their wet weight was measured. Then, the corresponding samples were placed in a constant temperature oven at 105℃ and dried to constant weight, and their oven-dry weight was measured.
[0067] The water retention value of each sample is calculated based on the difference between the wet weight and the oven-dry weight after centrifugation. The calculation formula is: Water retention value = (wet weight - dry weight) / dry weight × 100%.
[0068] Infrared spectroscopy was performed on each of the prepared slurry samples, with the scanning range set at 4000 cm⁻¹. -1 Up to 400cm -1 Examine 3200cm -1 Up to 3600cm -1 The shift and shape changes of the hydroxyl absorption peak within the region are used to analyze the destructive and recombination states of hydrogen bonds.
[0069] Experimental data: Table 1. Data on water retention value and infrared spectral characteristic peaks at different stages of fiber treatment Sample number Processing stage Water retention value (%) Wavenumber of hydroxyl absorption peak (cm⁻¹) A-1 Waste paper raw material (initial state) 123.7 3342.6 A-2 Waste paper raw materials (parallel sample) 121.2 3341.1 B-1 High-temperature medium-concentration slurry (after pulping) 172.8 3358.4 B-2 High-temperature medium-concentration slurry (parallel samples) 171.4 3357.2 C-1 Cooling and diluting the slurry (after rapid cooling) 168.9 3356.1 C-2 Cooling and diluting the slurry (parallel samples) 166.3 3354.8 D-1 Control sample (naturally and slowly cooled) 138.5 3346.7 D-2 Control sample (parallel sample) 141.2 3348.2 See appendix Figure 1 , Figure 1 The image shows the waste paper raw material, high-temperature medium-concentration pulp, and cooling diluted pulp in Example 2 at 3200 cm⁻¹. -1 Up to 3600cm -1 The shift of characteristic infrared spectral peaks within the region.
[0070] in conclusion: Based on the data in Table 1 and Figure 1 The distribution and analysis of water retention value data showed that, in its initial state, waste paper raw materials exhibited low water retention values due to irreversible internal keratinization and hydrogen bonding, reflecting a baseline state of limited shrinkage and swelling of fiber cell wall pores. After adding industrial urea aqueous solution and undergoing neutral high-temperature thermodynamic deconstruction, the water retention value of the obtained high-temperature medium-concentration pulp increased to approximately 172%. The corresponding infrared spectrum showed that the hydroxyl absorption peak increased from 3342.6 cm⁻¹. -1 It shifted to a higher wavenumber of 3358.4 cm. -1 This change indicates that industrial urea intervenes in the intersegments of cellulose chains under high-temperature conditions, interfering with the original hydrogen bond structure, promoting the opening of internal pores and the exposure of free hydroxyl groups, thus verifying the effectiveness of the high-temperature competitive substitution mechanism.
[0071] After implementing conformational locking with cold white water from the paper machine wire section, the water retention value of the cooled and diluted pulp remained in the range of approximately 167%, without a significant decrease. In contrast, the water retention value of the sample treated with natural cooling dropped to around 140%. Under conventional slow cooling conditions, fiber molecular chains rearrange with heat dissipation, easily inducing secondary keratinization and thus reducing water retention performance. This method, by incorporating cold white water from the paper machine wire section for rapid cooling, restricts the movement and recombination of molecular chain segments, effectively maintaining the open pore structure in a metastable open fiber conformation.
[0072] This high swelling state of the fiber, maintained through physical temperature intervention, directly increases the effective surface area and the number of active sites. Its structural characteristics provide ample anchoring space for the anhydrous calcium chloride solution to form coordination centers during the subsequent turbulent dispensing process in the delivery system, ensuring that the amphoteric starch solution can construct a uniformly distributed three-dimensional rigid network during the pulsed coordination crosslinking step.
[0073] Test Example 2: Charge and Particle Size Characteristics Tested During the Construction of Three-Dimensional Ion Coordination Networks Experimental steps: The following samples were extracted from Example 2: the cooled and diluted pulp that had undergone conformational locking by rapid cooling with cold white water in the paper machine wire section but had not yet been treated (referred to as samples E-1 and E-2); the pre-crosslinked pulp that had been injected with anhydrous calcium chloride solution by the pulp pump (referred to as samples F-1 and F-2); and the crosslinked pulp that had been continuously added with amphoteric starch solution through a pressure sieve (referred to as samples G-1 and G-2). The sample volume for each group was 200 mL. The samples were sealed immediately after sampling to prevent carbonic acid adsorption.
[0074] The slurry samples from each of the above stages were subjected to gravity filtration through a 200-mesh nylon screen, and the permeated filtrate was collected. Since the filtrate mainly contains dissolved and colloidal substances, fine fiber fragments, and added chemical additives, its double-layer characteristics can sensitively reflect the interfacial charge state before macromolecular crosslinking.
[0075] The collected filtrate sample was placed in a water bath and the water temperature was adjusted to 25°C to eliminate the interference of thermodynamic temperature on electrophoretic mobility. Using a micropipette, 1 mL of filtrate was slowly injected into the flow cell of the laser Doppler Zeta potentiometer, ensuring that no air bubbles were generated during the operation.
[0076] The Zeta potential meter was used to perform parallel measurements on each sample. Each measurement consisted of 15 pulse cycles, and the average value was taken as the final Zeta potential. The conductivity data of the system was recorded simultaneously to monitor the dynamic changes in ionic strength. Subsequently, a small amount of filtrate was extracted and transferred to a dynamic light scattering particle size analyzer to determine the hydrodynamic diameter distribution of fine particles in the system.
[0077] Experimental data: Table 2. Charge and conductivity data of the turbulent misaligned dosing and pulsed coordination crosslinking stages of the delivery system. Sample number Process flow stage Mean Zeta potential (mV) Electrical conductivity (mS / cm) Mean hydrodynamic diameter (nm) E-1 Cooling and diluting the slurry (base fluid) -23.4 1.18 214.5 E-2 Cooling and diluting the slurry (parallel samples) -22.7 1.21 221.3 F-1 Pre-crosslinked slurry (after calcium addition) -9.2 2.34 245.8 F-2 Pre-crosslinked slurry (parallel samples) -8.6 2.31 252.1 G-1 Cross-linked slurry (after adding starch) -1.8 2.15 1458.7 G-2 Crosslinked slurry (parallel samples) -2.4 2.19 1392.4 in conclusion: Based on the data in Table 2, observations of the cooled and diluted pulp without added agents revealed that the presence of residual lignin and trace amounts of anionic debris resulted in a strongly negative Zeta potential below -22mV. Under these conditions, although the pulp system could maintain dispersion through electrostatic repulsion, the active sites on the fiber surface were shielded by the anionic charge, making it difficult to spontaneously establish high-strength interlayer bonds.
[0078] After implementing the turbulent, staggered dosing process in the delivery system, the macroscopic conductivity of the pre-crosslinked slurry increased with the introduction of anhydrous calcium chloride solution, while its Zeta potential rapidly shifted towards zero to approximately -9 mV. At this point, the corresponding particle size data did not show a sudden change in magnitude. This phenomenon of dramatic charge change while maintaining particle size stability demonstrates that the Ca dissociation from the anhydrous calcium chloride solution... 2+ It primarily functions as a charge neutralizer and a targeted adsorbent. Under the high-frequency turbulent shear environment generated by the slurry pump, Ca...2+ It overcomes the resistance of the diffusion boundary layer, is uniformly anchored on the originally repulsive anion surface, and successfully pre-positions the coordination centers required for subsequent reactions.
[0079] In the subsequent pulse coordination crosslinking step, the addition of amphoteric starch solution fundamentally changed the crosslinking state of the system. Test results showed that the Zeta potential of the crosslinked slurry eventually stabilized in the slightly negative range of around -2mV. This charge state is beneficial for maintaining the stability of the fine fibers and the retention and filtration system.
[0080] The hydrodynamic diameter of the cross-linked slurry jumped from the 200 nm level to over 1400 nm. The phosphate ester anionic groups in the amphoteric starch macromolecular chain formed a dense and specific binding with the previously constructed coordination centers, while the quaternary ammonium cationic groups blocked the remaining anionic sites.
[0081] A series of fluid shear decoupling operations, while completely neutralizing the double electric layer, utilize the spatial expansion characteristics of polymer chains to firmly encapsulate the dispersed fine molecules, assembling a compact three-dimensional rigid network at the macroscopic level, providing a strength foundation for the dehydration molding process.
[0082] Test Example 3: Environmental Protection and Burden Reduction Effect Test of Cold White Water in Paper Machine Wire Section Experimental steps: Cold white water from the paper machine wire section discharged from below the forming wire during the dehydration and forming process of Examples 1, 2, 3, and Comparative Examples 1 and 2 was collected. The sample volume for each group was 1000 mL, and the samples were stored in polyethylene sampling bottles that had been washed with deionized water.
[0083] The collected cold white water samples from the wire section of each paper machine were immediately centrifuged at 4000 r / min for 20 min to remove suspended fine fibers and filler particles. The supernatant was then used as the test sample to ensure that the test results reflected the dissolved organic load.
[0084] The chemical oxygen demand (COD) of the supernatant sample was determined using the dichromate method (according to GB / T11914 standard). The supernatant to be tested, potassium dichromate standard solution, and silver sulfate catalyst solution were added sequentially to an Erlenmeyer flask, and the mixture was refluxed at 148°C for 2 hours.
[0085] After the reflux solution has cooled to room temperature, add ferricyanide indicator, titrate with ferrous ammonium sulfate standard solution, record the amount of titrant consumed, and calculate the chemical oxygen demand concentration of each sample.
[0086] The supernatant of each group was scanned at all wavelengths using a UV-Vis spectrophotometer, with the scanning range set from 200 nm to 400 nm. The absorbance value at 280 nm was recorded as a key point, and a UV-Vis scan spectrum was plotted. The absorption intensity distribution of lignin and hemicellulose degradation products dissolved in the cold white water of the paper machine wire section was characterized by the area-filled region.
[0087] Experimental data: Table 3. Data on Chemical Oxygen Demand and Ultraviolet Absorbance of Cold White Water in Paper Machine Wire Section for Each Group Sample group Chemical oxygen demand (COD) measured value 1 (mg / L) Chemical oxygen demand (COD) measured value 2 (mg / L) Chemical oxygen demand (COD) measured at 3 mg / L. Average absorbance at 280nm (au) Example 1 456.2 442.8 468.5 0.312 Example 2 412.4 425.1 418.9 0.285 Example 3 475.6 492.3 481.7 0.344 Comparative Example 1 1842.1 1925.6 1878.3 1.452 Comparative Example 2 621.5 645.2 615.8 0.528 See appendix Figure 2 , Figure 2 The image shows the light absorption intensity distribution of the dissolved components in Example 2, Comparative Example 1, and Comparative Example 2 in the wavelength range of 200 nm to 400 nm by filling regions of different depths.
[0088] in conclusion: Based on the data in Table 3 and Figure 2 The results show that Comparative Example 1 exhibits the largest dark gray filled area in the 200nm to 300nm region, with an absorbance peak of 1.452au near 280nm and a corresponding average chemical oxygen demand (COD) concentration exceeding 1880mg / L. This high absorption intensity and high COD value indicate that under the strongly alkaline treatment environment used in Comparative Example 1, the hemicellulose and lignin components in the waste paper raw material underwent a violent peeling reaction. A large amount of macromolecular organic matter dissolved into the cold white water of the paper machine wire section due to chemical degradation, forming the main body of dissolved and colloidal substances in the closed-loop white water system.
[0089] Example 2 is characterized by the bottommost light gray filled region, with a flat spectral curve and low absorbance, and a chemical oxygen demand (COD) concentration of only about 418.9 mg / L. This trend reflects the superiority of the neutral high-temperature thermodynamic decomposition mechanism, namely, using industrial urea aqueous solution as a ionizing swelling agent to selectively replace hydrogen bonds at the molecular level, thereby avoiding the breaking of covalent bonds. Because the neutral system inhibits the alkaline degradation of plant fiber components, the generation of dissolved organic matter is limited.
[0090] Comparative analysis of Comparative Example 2, which did not use industrial urea, revealed that its spectral filling area (middle gray region) was significantly higher than that of the Example Group, and its chemical oxygen demand concentration also increased to approximately 620 mg / L. This phenomenon indicates that without efficient swelling methods, waste paper raw materials will experience more fine fiber loss due to uneven stress during subsequent physical disintegration, increasing the solids load on the cold white water of the paper machine wire section. This process ensures the flexibility of the fiber structure through thermodynamic decoupling and conformational quenching locking, effectively reducing the pollution pressure of the white water system while maintaining the physical strength of the product, thus achieving the goal of clean production in the waste paper recycling process.
[0091] Test Example 4: Macroscopic Mechanical Strength Improvement Test of White Board Paper Base Paper Experimental steps: Whiteboard paper base paper obtained from the heat shrink curing and drying process of Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, and 5 was selected as test samples.
[0092] According to the requirements of GB / T10739 standard, all whiteboard paper samples were placed in a constant temperature and humidity laboratory at 23±1℃ and 50±2% for 24 hours to allow the internal stress of the paper fibers to be fully released and reach a stable moisture balance state.
[0093] Using a standard paper cutter, ring crush strength specimens with dimensions of 152.0±0.2mm×12.7±0.1mm and interlaminar bond strength specimens with dimensions of 25.4±0.5mm×125±5mm were cut from each group of samples along the longitudinal and transverse directions. The number of valid test specimens for each group of samples shall not be less than 10.
[0094] Using a compressive strength tester, insert the ring crush strength specimen into the annular specimen holder and apply pressure at a constant speed of 12.5±2.5 mm / min until the specimen is crushed. Record the maximum pressure value and calculate the ring crush strength index based on the specimen weight.
[0095] The Scott interlaminar bond strength tester was used to perform vertical impact tests on the specimens. The specimens were attached between a special base and an aluminum corner, and the specimens were delaminated by impact with a pendulum. The potential energy difference before and after the pendulum was released was recorded, and the interlaminar bond strength value was directly read.
[0096] Experimental data: Table 4. Test data of physical strength properties of whiteboard paper base paper for each group Sample group Mean ring crush strength index (N·m / g) Mean interlayer bond strength (J / m2) Tightness (g / cm3) Example 1 8.71 245.6 0.584 Example 2 11.32 334.7 0.648 Example 3 9.88 291.3 0.621 Comparative Example 1 6.11 158.2 0.487 Comparative Example 2 7.42 205.4 0.545 Comparative Example 3 6.71 178.5 0.518 Comparative Example 4 8.59 232.7 0.592 Comparative Example 5 8.08 225.1 0.578 in conclusion: According to the data in Table 4, the whiteboard paper base paper produced by this process shows a coordinated improvement trend in both mechanical strength and paper density.
[0097] Example 2 represents the largest area enveloped by the solid dot pattern, corresponding to an average ring crush strength index of 11.32 N·m / g and an interlayer bond strength of 334.7 J / m. 2 This demonstrates the effectiveness of the neutral high-temperature thermodynamic deconstruction and conformational quenching locking mechanism in improving paper performance. In Comparative Example 3, due to the lack of rapid cooling intervention using cold white water from the paper machine wire section, the fibers underwent secondary keratinization during the slow cooling process. This caused the open conformation of the metastable fibers, originally stretched by the industrial urea solution, to shrink, reducing the opportunity for the anhydrous calcium chloride solution to enter the fiber interior and build coordination centers, ultimately preventing the construction of a dense three-dimensional rigid network.
[0098] Based on the data from Comparative Example 4, it lags behind Example 2 in both ring compression strength and interlayer bonding strength. After abandoning the turbulent misalignment of the delivery system for drug addition, divalent calcium ions and amphoteric starch slurry are prone to localized irrational flocculation due to overlapping drug addition points in the absence of high-frequency turbulent shearing. This uneven cross-linking state prevents the establishment of a uniformly distributed three-dimensional ion coordination network in the subsequent physical shrinkage of the wet paper web.
[0099] Based on the data from Comparative Example 5, it can be confirmed that even under the same processing conditions, the interlayer bonding strength of single cationic starch is only 225.1 J / m. 2 This proves that the phosphate anion groups in amphoteric starch react with Ca... 2+ Establishing coordinate bonds is key to enhancing the rigidity of paper.
[0100] This solution optimizes the overall mechanical properties of whiteboard paper base paper by controlling the temperature gradient and fluid shear environment to ensure the orderly anchoring of each chemical component on the fiber surface.
Claims
1. A whiteboard paper composite pulping and papermaking process, characterized in that, Includes the following steps: Waste paper raw materials are atomized and sprayed with industrial urea aqueous solution for high-concentration impregnation in the dry zone to obtain pre-impregnated waste paper raw materials; The preimpregnated waste paper raw material is injected into hot water for neutral high-temperature thermodynamic decomposition to obtain high-temperature medium-concentration pulp. Cold white water from the wire section of a paper machine is mixed into the high-temperature medium-concentration slurry to perform rapid cooling and conformation locking of the cold white water, thereby obtaining a cooled and diluted slurry. Anhydrous calcium chloride solution is injected into the cooled and diluted slurry through a turbulent staggered dosing system, and a pre-crosslinked slurry is obtained by high-frequency turbulent shearing by the impeller of the slurry pump. Amphoteric starch solution is added dropwise to the pre-crosslinked slurry, and pulse coordination crosslinking is completed by high-frequency fluid pulse shearing through a pressure screen rotor to obtain a crosslinked slurry; The cross-linked slurry is dehydrated and shaped to obtain a wet paper web, and the wet paper web is heat-shrinked, cured and dried to obtain whiteboard paper base paper.
2. The whiteboard paper composite pulping and papermaking process according to claim 1, characterized in that, The dosage of each component is calculated based on the oven-dry pulp mass of the waste paper raw material: The dry weight usage of industrial urea is 1.0%-1.5%, the dry weight usage of anhydrous calcium chloride is 0.2%-0.3%, and the dry weight usage of amphoteric starch is 1.2%-1.5%.
3. The whiteboard paper composite pulping and papermaking process according to claim 2, characterized in that, The industrial urea aqueous solution has a mass concentration of 20%-30%; The anhydrous calcium chloride solution has a mass concentration of 5%-10%; The mass concentration of the amphoteric starch solution is 1%-2%.
4. The whiteboard paper composite pulping and papermaking process according to claim 1, characterized in that, The preparation steps of the amphoteric starch include: Industrial raw starch is added to room temperature water and mechanically mixed to obtain a starch milk with a mass concentration of 35%-40%. Add a 3% sodium hydroxide solution to the starch milk to adjust the pH of the system to 11.0-11.5, then slowly add 3-chloro-2-hydroxypropyltrimethylammonium chloride and heat to 45℃-50℃ for a constant temperature reaction for 4-6 hours to obtain cationic starch milk; Sodium tripolyphosphate was added to the cationic starch milk, and the reaction was continued at a constant temperature of 45℃-50℃ for 2-3 hours to obtain amphoteric starch slurry.
5. The whiteboard paper composite pulping and papermaking process according to claim 4, characterized in that, The preparation steps of the amphoteric starch further include: Add 10% (w / w) dilute hydrochloric acid to the amphoteric starch slurry to adjust the pH of the system to 6.0-6.5 for neutralization to terminate the reaction; The starch was then centrifuged and dehydrated, washed 2-3 times with clean water, and finally dried at 60°C using an airflow dryer to evaporate the moisture to below 12%, thus obtaining the amphoteric starch.
6. The whiteboard paper composite pulping and papermaking process according to claim 1, characterized in that, The waste paper raw materials are selected from one or more physical mixtures of old corrugated cardboard boxes, mixed waste paper and waste newspapers; The high-concentration impregnation in the dry zone is performed on the conveyor belt, and the natural surface penetration time is 2-3 minutes.
7. The whiteboard paper composite pulping and papermaking process according to claim 1, characterized in that, The neutral high-temperature thermodynamic decomposition is performed inside a hydraulic pulper, with the injected hot water temperature at 65℃-70℃, the pulp mass concentration controlled at 8%-12%, the system pH maintained at 6.5-7.5, and the hydraulic pulping is continuously carried out for 15-20 minutes at a mixed temperature of 55℃-60℃.
8. The whiteboard paper composite pulping and papermaking process according to claim 1, characterized in that, The rapid cooling conformation of the cold white water is locked along the pumping line and at the inlet of the pulping tank. The volume ratio of the high-temperature medium-concentration pulp to the cold white water in the paper machine wire section is 1:2 to 1:
3. The temperature of the cold white water in the paper machine wire section is 20℃-25℃, so that the system temperature drops below 30℃ and the concentration is diluted to 3%-4%.
9. The whiteboard paper composite pulping and papermaking process according to claim 1, characterized in that, The shear rate of the high-frequency turbulent shearing is greater than or equal to 1000 s. -1 The material is further diluted to a concentration of 0.8%-1.2% in a slurry pump to obtain the pre-crosslinked slurry.
10. The whiteboard paper composite pulping and papermaking process according to claim 1, characterized in that, The dehydration and molding process is performed by spraying material into the forming screen from a headbox. The heat shrink curing and drying are performed in the pressing section and the drying cylinder section, with the heat transfer temperature controlled at 80℃-110℃ until the whiteboard paper base paper is wound up.
Citation Information
Patent Citations
Process for the production of paper or paperboard, paper or paperboard product obtained and uses thereof
CN107849824A
Improved papermaking process
EP0805234A2